E-Government Development Index (EGDI) and its relationship with the economic development level in the EAEU countries - O. V. Azoeva; K. K. Nurasheva; G. A. Shim (Вестник университета, 2022)
Modern digital technologies have become an important factor in improving the quality of public administration in the services provision by government bodies and structures and in ensuring sustainable development and economic growth. There is a certain relationship between the level of the government digitalization and the economic development level of the country. The scale and speed of the digital technology introduction is largely determined by the level of economic development. In turn, the quality and volume of public services provided make it possible to more fully and efficiently use the society potential in the economic development interests of the country and its citizens. The article is devoted to the analysis and identification of the relationship nature between the development of e-government and the economic development level in the Eurasian Economic Union (EAEU) countries, and the assessment of these characteristics’ interconnection closeness. The article was applied methodological approaches and key indicators used by the United Nations (UN) to assess the information society development level. A comparative analysis of the e-government development indices (EGDI) and gross domestic product per capita in the EAEU countries from 2010 to 2020 was carried out. The dynamics of change and the relationship of these indicators was investigated. The Electronic Government Index (EGDI) is considered in terms of its three main components (subindices): the online public services development level (Online Service Index), the telecommunications infrastructure development level (Telecommunication Infrastructure Index), the human capital development level (Human Capital Component). Based on the results obtained, conclusions were formulated and the prospects for further changes in these indicators in the new social and economic conditions were considered.